Caracterização e análise da participação e dos conflitos em uma escola transformada em comunidades de aprendizagem - Pinheiro, Edneia Virginia (Universidade Federal de São Carlos, 2010)
The objective of this study is to understand the impact of Learning Communities (LC) in a school unit in relation to participation and the conflicts existing within them, highlighting in particular those aspects which facilitate and hamper the manifestation and resolution of the conflicts. Taking as reference the critical communicative methodology, and based on the communicative action concepts, of Habermas, and dialogicity, of Freire, the principal means of data collection of this research was in-depth interviews, carried out with: the head of the EMEB, the deputy director, a schoolmistress, who had been acting for approximately two years as pedagogical coordinator, and a family member. All the people interviewed were involved in one of the unit s two bodies (School Council or Management Commission). We sought, in this way, to understand the existing relationship between the participation of everyone in the school and in the decision-making processes, in a egalitarian manner, and the occurrence of conflicts, seeking to identify which factors stimulate conflicts and which factors inhibit them, and how they manifest themselves in the relations within the unit and in what way the egalitarian dialogue, present in the decision processes of a LC, impacts on these conflicts. The analysis of the data, which embraced both transformative factors and those that appeared as obstacles to transformation, took the form of a collaboration between the individuals interviewed and the researcher, in order to promote dialogue on the content raised, the themes chosen and the understandings reached, aiming for consensus. We were able to observe that many changes occurred in the school unit following the implementation of the LC proposal. Noteworthy among them is the incorporation of egalitarian dialogue in all the relationships, involving the different bodies of the EMEB. We observed that the existence of conflicts in the unit demonstrates its openness to dialogue, enabling everyone to state their opinions and arguments. Conflict, therefore, has acted as a point of departure in the search for understanding, which is established with the communicative action, the fruit of consensus reached by means of the best arguments. This investigation integrates the research Learning communities: a wager on the quality of learning, on the equality of difference and on the democratization of school management , which envisages four axes of investigation: (1) learning to read and write, (2) dialogic learning practices, (3) formative needs and educational potentialities of the surrounding population, with focus on the working conditions of family members and on the environmental conditions and ways of life in that environment, (4) management and participation of the community in the life of the school.
Keywords: Escolas - organização e administração; Participação; Conflito - administração; Gestão democrática; Democratic management; Conflict; Participation; CIENCIAS HUMANAS::EDUCACAO